DEGRADATION OF WILLS OF WILLS FROM AUTHENTIC DEEDS BECOME PRIVATE LETTER BASED ON COURT DECISIONS AND IMPLEMENTATION OF IMPLEMENTATION IN THE DIVISION OF INHERITED ASSETS (Case Study of Supreme Court Decision Number: 3466 K/Pdt/2016 - Sunardi, Sunardi; Muhibbin, Moh.; Wanura, Gabriel Ibrizul (International Significance of Notary, 2022)
An authentic deed if the making is not in accordance with the statutory provisions of Law No. 2 of 2014 concerning the Position of Notary Public and the Civil Code, then the deed can be null and void by law, can be canceled or even the deed has decreased strength of evidence to become a private letter or in other words experiencing deed degradation.Formulation of the problem How Does the Degradation of Deeds of Wills Happen From Authentic Deeds to Private Letters Based on the Supreme Court Decision Number 3466 K/PDT/2016. And what is the impact and application of the inheritance from the deed of testamentary grants after experiencing degradation from an authentic deed to a private letter.In writing this thesis using normative research methods. The results of the research were the Degradation of Wills and Grants Deeds from Authentic Deeds to Private Letters Based on the Supreme Court Decision Number 3466 K/PDT/2016. Because in making a deed it does not meet the formal and material requirements and is contrary to the laws and regulations of Law no. 2 of 2014 and the Civil Code, especially Articles 1868 and 1869 of the Civil Code that apply. This resulted in the authentication of the deed as perfect evidence not occurring so that it became an underhanded deed. in the case at the Supreme Court with case number 3466 K/PDT/2016, that the Deed of Willing Grant (legaat) Number 6 dated 9 December 2005 made before Sigit Siswanto, S.H., Notary in Depok City has been proven not to comply with the provisions of the Law on Notary Position in its making and has complied with the provisions in Article 1868 and Article 1869 of the Civil Code, which causes the legal deed to become a private letter.The Impact of Application of Inheritance From Deeds of Wills After Experiencing Degradation from Authentic Deeds to Underhanded Letters. As a result of the deed becoming a deed under the hand In the distribution of inheritance from a testamentary grant, additional evidence is needed so that the distribution of the inheritance from a will can be carried out. Based on the case in the case at the Supreme Court with case number 3466 K/PDT/2016 due to the Deed of Statement Number 6 dated 8 October 2007 made before Theresia Siti Rahayu, S.H. Notary in Jakarta, and strengthened by a sufficiently stamped statement dated October 8, 2007 which was made privately by the plaintiff, which essentially stated that the defendant was subject to the Deed of Wills and Grants. In accordance with Article 1875 of the Civil Code, that if an underhanded letter is recognized or legally justified, in this case with the presence of other evidence, it will cause complete proof such as an Authentic Deed or become perfect proof.Keywords: Authentic Deed, Under Hand, Will Grant.